Estrategias de comunicación para el personal de Enfermería que atiende personas sordas. - Ma. Cristina Méndez Blanco; Ericka Ortíz López; Alejandra Venegas Vindas (Universidad de Costa Rica, 2012)
This article represents the results of implementing a program based on communication strategies for staff of nursing care for people with hearing impairment attending the National Children?s Hospital Dr. Carlos Saenz Herrera. We applied an initial and final assessment to eight female participants to determine their knowledge about effective communication with deaf people. One of the main results found is that when nurse provide care to people with hearing impairments, nursing staff may feel frustration, helplessness, anxiety, fear and failure, since it requires more work, time and resources to provide care to this population. Concluding that when deaf people try to get health services they do not receive an intervention according to their limitations in their ability to communicate, plus most of the nursing staff who assist them do not have tools to establish effective communication.